Acupressure Assistance To Smooth The Expenditure Of Breast Milk For Breastfeeding Mothers In Aceh Besar Regency - Noviyanti yanti; Nurdahlina (Institute of Computer Science (IOCS), 2022)
The coverage of exclusive breastfeeding in Aceh in 2021 is recorded at 66.6 percent which is still below the national target of 80 percent. One of the causes of low breastfeeding is experiencing non-smooth milk expenditure which causes anxiety for the mother. One effort that can be used to increase milk production is using the acupressure technique. The method used for individual assistance is to make home visits to postpartum mothers who experience non-fluent breastfeeding. The activity begins with an assessment of mothers' perceptions about breastfeeding, counseling about the breastfeeding process and teaching acupressure to increase milk production. The results of the activity after providing assistance 2-5 times to 10 postpartum mothers, 100% experienced smooth breastfeeding. as many as 6 people (60%) experienced smooth breastfeeding on the third day, 30 percent on the fourth day and the last 10 percent on the fifth day. After carrying out individual assistance which began with an assessment of the mother's perception of breastfeeding, counseling on the breastfeeding process and teaching acupressure to increase milk production, the results obtained were 100% of postpartum mothers could perform acupressure and express breastfeeding for postpartum mothersfluent.